What Explains the Growing Gender Education Gap? The Effects of Parental Background, the Labor Market and the Marriage Market on College Attainment - Zvi Eckstein; Michael P. Keane; Osnat Lifshitz (Institute of Labor Economics (IZA), 2023)
In the 1960 cohort, American men and women graduated from college at the same rate, and this was true for Whites, Blacks and Hispanics. But in more recent cohorts, women graduate at much higher rates than men. To understand the emerging gender education gap, we formulate and estimate a model of individual and family decision-making where education, labor supply, marriage and fertility are all endogenous. Assuming preferences that are common across ethnic groups and fixed over cohorts, our model explains differences in all endogenous variables by gender/ethnicity for the '60-'80 cohorts based on three exogenous factors: family background, labor market and marriage market constraints. Changes in parental background are a key factor driving the growing gender education gap: Women with college educated mothers get greater utility from college, and are much more likely to graduate themselves. The marriage market also contributes: Women's chance of getting marriage offers at older ages has increased, enabling them to defer marriage. The labor market is the largest factor: Improvement in women's labor market return to college in recent cohorts accounts for 50% of the increase in their graduation rate. But the labor market returns to college are still greater for men. Women go to college more because their overall return is greater, after factoring in marriage market returns and their greater utility from college attendance. We predict the recent large increases in women's graduation rates will cause their children's graduation rates to increase further. But growth in the aggregate graduation rate will slow substantially, due to significant increases in the share of Hispanics – a group with a low graduation rate – in recent birth cohorts.
Keywords: J08; J12; J21; E24; 330; returns to college; parental background; college graduation; education; gender wage gap; assortative mating; labor supply; marriage; fertility